2016
DOI: 10.1002/pnp.430
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of schizophrenia - a review of progress

Abstract: Since much of our knowledge about the neurobiology of schizophrenia derives from the initial discovery that chlorpromazine was effective in treating psychosis, pharmacological research has mostly concentrated on dopamine-blocking agents. Here, the authors discuss the situation where there is no single pharmacological agent on the horizon that could serve as the 'holy grail' to address the full range of symptoms of schizophrenia and what the immediate future holds with the widespread use of polypharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The ideal situation would be to have medication that addresses the symptoms of psychosis with minimal side effects. However, due to a lack of fundamental innovation in psychopharmacology during recent decades, we still have to work with antipsychotics with a range of motor, metabolic, and cognitive side effects (28, 44). Moreover, as there is still an overall favorable benefit-to-risk ratio for the use of antipsychotics (45), addressing lifestyle is of importance to help minimize such side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal situation would be to have medication that addresses the symptoms of psychosis with minimal side effects. However, due to a lack of fundamental innovation in psychopharmacology during recent decades, we still have to work with antipsychotics with a range of motor, metabolic, and cognitive side effects (28, 44). Moreover, as there is still an overall favorable benefit-to-risk ratio for the use of antipsychotics (45), addressing lifestyle is of importance to help minimize such side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its unique overall treatment concept and personalized drug composition for different patients, it is a good adjuvant therapy which shows substantial promise to improve clinical outcomes. Western medicine mainly treats chronic schizophrenia with atypical antipsychotic drugs such as aripiprazole, risperidone, olazine, and typical antipsychotic drugs like chlorpromazine and haloperidol, which are effective for first-episode schizophrenia, but not ideal for chronic schizophrenia ( Dimitrelis and Shankar, 2016 ). Numerous studies have suggested that the utilization of Chinese herbs in conjunction with western antipsychotics is beneficial in terms of mental state, holistic functioning, and decrease of adverse effects ( Rathbone et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lumateperone (4-((6b R ,10a S )-3-methyl-2,3,6b,9,10,10 a -hexahydro-1 H ,7 H -pyrido[3′,4′:4,5]pyrrolol[1,2,3- de ]-quinoxalin-8-yl)-1-(4-fluoro-phenyl)-butan-1-one 4-methylbenzenesulfonate), 43 also known as ITI-007 and ITI-722, exists as the tosylate salt 5,20,36,37,44 (Figure 1). The principal metabolite of lumateperone, ICI200131, is the alcohol produced by the reduction of the carbonyl side-chain by ketone reductase.…”
Section: Methodsmentioning
confidence: 99%
“…Those are common targets of other antipsychotic drugs that may cause adverse effects like weight gain, sedation, and orthostatic hypotension. 37 It displays a moderate binding affinity for dopamine D 4 and α-1 A and α-1 B adrenergic receptors (Ki protected at <100 nM), with a low binding affinity (<50% inhibition at 100 nM) for muscarinic and histaminergic receptors. 24…”
Section: Pharmacodynamicsmentioning
confidence: 99%
See 1 more Smart Citation